2014
DOI: 10.1186/gm559
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide mutational landscape of mucinous carcinomatosis peritonei of appendiceal origin

Abstract: BackgroundMucinous neoplasms of the appendix (MNA) are rare tumors which may progress from benign to malignant disease with an aggressive biological behavior. MNA is often diagnosed after metastasis to the peritoneal surfaces resulting in mucinous carcinomatosis peritonei (MCP). Genetic alterations in MNA are poorly characterized due to its low incidence, the hypo-cellularity of MCPs, and a lack of relevant pre-clinical models. As such, application of targeted therapies to this disease is limited to those deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
98
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 42 publications
15
98
4
Order By: Relevance
“…Molecular analysis of the neoplastic cells demonstrated identical K-ras mutations in both the ovarian and appendiceal neoplasms. Further, loss of heterozygosity occurred in both the appendiceal and ovarian neoplasms in all cases except for one where there was preservation of both alleles in the appendix [12,13]. This was attributed to a loss of heterozygosity as a part of tumor progression by the ovaries.…”
Section: Discussionmentioning
confidence: 84%
“…Molecular analysis of the neoplastic cells demonstrated identical K-ras mutations in both the ovarian and appendiceal neoplasms. Further, loss of heterozygosity occurred in both the appendiceal and ovarian neoplasms in all cases except for one where there was preservation of both alleles in the appendix [12,13]. This was attributed to a loss of heterozygosity as a part of tumor progression by the ovaries.…”
Section: Discussionmentioning
confidence: 84%
“…Its mutation was originally found in pituitary tumors, intraductal papillary mucinous neoplasms of the pancreas (IPMN), gastric, and intestinal adenomas as well as CRC. 20 Prevalence of KRAS & GNAS mutations in LAMN and PMP tumor samples has been reported in various studies with high variability ranging from 53-100% & 40-63% respectively (Table 1). [21][22][23][24][25][26] Differences in cell enrichment methods, genomic sequencing techniques, regional variation and small number patients in most of these studies may have contributed to this variation.…”
Section: Pseudomyxoma Peritonei Genomicsmentioning
confidence: 91%
“…Alakus et al reported KRAS and GNAS mutations in 10/10 and 9/10 tumor samples respectively, which is quite higher than previous studies. 20 It may be quite possible that due to hypocellular nature of this disease, prevalence of these mutations may have been underestimated in other studies. However, APC and p53 mutation are uncommon in PMP of appendiceal origin in contrast to colon cancer.…”
Section: Pseudomyxoma Peritonei Genomicsmentioning
confidence: 98%
See 1 more Smart Citation
“…[10] Overexpression of p53 is reported to be rare in appendiceal tumours and, although KRAS mutation and p53 overexpression can be seen in half of PMP cases of appendiceal origin. [11] Microsatellite instability has also been shown to be rare in appendiceal carcinoma, and hyper-methylation is not a mechanism for genetic instability in these tumours although some hyperplastic polyps and sessile serrated adenomas of the appendix show decreased expression of MLH1 and BRAF mutation is more common in serrated polyps. [7] The only consistent risk factor identified for appendiceal cancer is increasing age.…”
Section: Discussionmentioning
confidence: 99%